2019
DOI: 10.1016/j.jss.2018.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Negative-Pressure Wound Therapy in Infants and Children: A Population-Based Study

Abstract: Background: Although the safety and benefits of negative pressure wound therapy (NPWT) have been clearly demonstrated in the adult population, studies evaluating the safety and describing the use of NPWT in the pediatric population have been limited. Given this paucity, the goals of this study were to: (1) evaluate the literature dedicated to NPWT use in infants and children; and (2) leverage a population-level analysis to describe the experience of NPWT use in the pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 119 publications
0
12
0
Order By: Relevance
“…Since its introduction in 1997 ( 16 , 17 ), the vacuum technique has been subject to a large spectrum of applications in the adult population. However, it has not yet proven the same efficacy and safety in children ( 18 ). Nonetheless, the literature on the efficacy of vacuum therapy seems promising in terms of the treatment of complicated pediatric wounds as pressure ulcers, extremity wounds, surgical wound dehiscence, skin grafting, or complex abdominal defects ( 9 11 , 19 21 ) and also congenital abdominal wall defects ( 5 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction in 1997 ( 16 , 17 ), the vacuum technique has been subject to a large spectrum of applications in the adult population. However, it has not yet proven the same efficacy and safety in children ( 18 ). Nonetheless, the literature on the efficacy of vacuum therapy seems promising in terms of the treatment of complicated pediatric wounds as pressure ulcers, extremity wounds, surgical wound dehiscence, skin grafting, or complex abdominal defects ( 9 11 , 19 21 ) and also congenital abdominal wall defects ( 5 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pain represents a common concern surrounding the use of NPWT in children 44 . Encouragingly, the results showed that procedures involving NPWT were not perceived by clinicians, caregivers or children as significantly more painful than standard dressing changes.…”
Section: Discussionmentioning
confidence: 99%
“…Negative pressure wound therapy is widely used for pediatric patients and has a low frequency of serious complications 2 . However, we found that the extensive VAC system from the abdominal to chest walls decreased the compliance of the chest wall.…”
Section: Discussionmentioning
confidence: 67%
“…By providing negative pressure to the wound tissue, NPWT improves blood flow, promotes granulation tissue, and decreases edema and bacterial counts 1 . Because NPWT has a low occurrence of serious complications, it is widely used in infants and can be effectively used in surgical and nonsurgical disciplines 2 . Indeed, when NPWT is used for the treatment of post‐sternotomy wounds, NPWT reduces the need for mechanical ventilation by closing the thoracic cavity 3–5 .…”
Section: Introductionmentioning
confidence: 99%